Combined osmotic pretreatment and hot air drying: Evaluation of drying kinetics and quality parameters of adajamir (Citrus assamensis) - J. Nudar; M. Roy; S. Ahmed (Heliyon, 2023)
Adajamir (Citrus assamensis) is a highly perishable but nutritional fruit. Hot air drying is ubiquitous in food preservation but not quality friendly. However, drying pretreatments play an indispensable role preserving fruits and vegetables. The aim of this study was, therefore, to reveal the hot air drying kinetics of osmotically pretreateated adajamir and investigate the quality parameters (total phenolic contents, antioxidant capacity, and vitamin C). Adajamir slices were subjected to osmotic pretreatment (10% sucrose, 10% fructose, and 2% NaCl), subsequently, dried in a hot air dryer at 50 °C, 30% relative humidity (RH), and with a velocity of 1 ms−1. The drying kinetics were studied using three mathematical models: Newtonian model, Henderson and Pabis model, and Page model. The result depicted that effective diffusivity was highest (9.5 ± 0.2a × 10−6 m2s−1) in untreated samples compared to the treated samples, and the Page model was the one with the best fitness to explain the drying behavior. Regarding quality, the pretreatments provided better retention of all quality parameters compared to the untreated samples. In addition, osmotic treatment with sucrose had the best quality retention capability. The study will contribute to the optimization of thermal processing parameters in fruit dehydration. Eventually, this research will expedite future research pertinent to innovative combined drying techniques of citrus fruit.